Impact of non surgical periodontal therapy on glycemic control in individuals with type 2 diabetes mellitus and periodontitis - Rafael Paschoal ESTEVES LIMA; Karolina Skarlet Silva VIANA; Pierre Geraldo Braz da SILVA JUNIOR; Luís Otávio Miranda COTA; Fernando Oliveira COSTA (Journal of Applied Oral Science)
Abstract The infectious and inflammatory process of the periodontal tissues can contribute to hyperglycemia in patients with diabetes. Objective The objective of this study was to evaluate the effect of non-surgical periodontal therapy on glycemic control in individuals with type 2 diabetes mellitus. Methodology In this clinical trial with two months of follow-up, 31 participants were included, with 15 having adequate glycemic control and 16 inadequate glycemic control. The participants underwent non-surgical periodontal therapy. Biological, social, and behavioral variables were collected. Periodontal clinical examination was performed at baseline and two months after the intervention. Laboratory tests to assess serum levels of glycated hemoglobin, fasting glucose, and C-reactive protein were requested for all participants at baseline and two months after periodontal treatment. Results The difference in glycated hemoglobin levels between baseline and two months after non-surgical periodontal therapy was statistically significant in the total sample (p=0.045) and in the group of individuals with adequate glycemic control (p=0.016). No significant difference was observed in glycated hemoglobin levels in the group of individuals with inadequate glycemic control. No significant variation was observed in fasting glucose and C-reactive protein levels after treatment in the studied sample. A reduction in probing depth, gingival inflammation, and gain in clinical attachment was observed in the total sample and in both groups according to glycemic control. Conclusion Periodontal intervention may contribute to improved glycemic control in individuals with type 2 diabetes mellitus and periodontitis (Brazilian Clinical Trials Registry RBR-9fvwk4m).